Effect of Curcumin on Interleukin-6 Expression and Malondialdehyde Levels in Liver Fibrosis - Aurellia, Natasha; Susilaningsih, Neni; Prabowo, Erik; Muniroh, Muflihatul; Budiono, Bernadus Parish (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Chronic inflammation and excessive oxidative stress are the main mechanisms causing liver fibrosis. It releases anti-inflammatory cytokines, namely, interleukin 6 (IL-6), nitric oxide, and malondialdehyde (MDA). Curcumin acts as an anti-inflammatory, antioxidant, and antifibrotic. AIM: This study is aimed to analyze differences in IL-6 expression and MDA levels in (Deutschland, Denken, and Yoken) DDY mice with liver fibrosis after common bile duct ligation between the curcumin-treated and control groups. METHODS: This research is an experimental study with a post-test-only control group design. Seventy-five male DDY mice 20–30g were used in this study (n = 5). Mice were randomly divided into five groups, each consisting of 15 mice. The first group healthy control (HC) was the HC group given phosphate-buffered saline (PBS) solution and did not perform the CBDL. The second group negative control (NC) was a NC group given PBS solution and completed the CBDL. The third group positive control (PC) was a PC group given oral ursodeoxycholic acid (UDCA) and performed CBDL. The fourth group (P1) was assigned oral curcumin and performed the CBDL. The fifth group (P2) was given oral curcumin and UDCA and performed the CBDL. Seven, fourteen, and 21 days after ligation, liver samples were taken to examine IL-6 expression and MDA levels. RESULTS: There was a significant difference between the NC and PC groups (p = 0.00), NC and P1 (p = 0.00), NC with P2 (p = 0.00), PC with P1 (p = 0.04), PC with P2 (p = 0.04), on day 21 between the NC and PC groups (p = 0.00), NC with P1 (p = 0.00), and PC with P2 (p = 0.00). Statistical analysis of the comparison of MDA levels on days 7 and 14 found no significant difference. On day 21, there was a substantial difference between the NC group and P1 (p = 0.02). CONCLUSION: This study concluded that curcumin effectively reduced IL-6 expression and MDA levels in liver fibrosis.